2001
DOI: 10.1113/jphysiol.2001.012990
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response of renal sympathetic nervous activity to aortic depressor nerve stimulation in the anaesthetized rat

Abstract: 1. The contribution of central baroreceptor reflex pathways to the dynamic regulation of sympathetic nervous activity (SNA) has not been properly examined thus far. The aim of this study was to characterize the transfer function of the central arc of the baroreceptor reflex (from baroreceptor afferent activity to SNA) over a wide range of frequencies. 2. In nine baroreceptor-intact and six sino-aortic baroreceptor-denervated rats anaesthetized with urethane, the renal SNA was recorded while applying sinusoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 0 publications
1
32
1
Order By: Relevance
“…In both humans and rats, SNA contains at least two rhythms that derive from the activity of the arterial baroreceptor reflex: a fast one synchronous with the cardiac beat (ϳ1 Hz in humans; 5-7 Hz in rats), and a slower one accompanying the vasomotor waves of AP usually termed Mayer waves (ϳ0.1 Hz in humans; ϳ0.4 Hz in rats). It has been shown in rats that sinoaortic baroreceptor denervation abolishes both rhythms when SNA is recorded from a renal nerve (22,28,42). However, only the pulsesynchronous oscillation can be regarded as reflecting the openloop operation of the baroreceptor reflex because of the lowpass filter properties of the resistance vasculature that prevent fluctuations of SNA to be translated into corresponding fluctuations of AP at frequencies above 1 Hz (21,23).…”
mentioning
confidence: 98%
“…In both humans and rats, SNA contains at least two rhythms that derive from the activity of the arterial baroreceptor reflex: a fast one synchronous with the cardiac beat (ϳ1 Hz in humans; 5-7 Hz in rats), and a slower one accompanying the vasomotor waves of AP usually termed Mayer waves (ϳ0.1 Hz in humans; ϳ0.4 Hz in rats). It has been shown in rats that sinoaortic baroreceptor denervation abolishes both rhythms when SNA is recorded from a renal nerve (22,28,42). However, only the pulsesynchronous oscillation can be regarded as reflecting the openloop operation of the baroreceptor reflex because of the lowpass filter properties of the resistance vasculature that prevent fluctuations of SNA to be translated into corresponding fluctuations of AP at frequencies above 1 Hz (21,23).…”
mentioning
confidence: 98%
“…In 6 of 10 rats, an inverse relationship was found between HR and phase (R = −0.27 ± 0.05; P < 0.05). A previous study on the transfer function between aortic depressor nerve stimulation and RSNA (Petiot et al, 2001) showed that phase was highly dependent on frequency near HR. Thus, HR variability could explain to a certain degree phase variability.…”
Section: Variability Of Sbrsmentioning
confidence: 98%
“…In particular, SNA contains a fast rhythm synchronous with the heart beat. At least in rats, this rhythm is entirely generated by the baroreceptor reflex because it is abolished after sinoaortic baroreceptor denervation when SNA is recorded from a renal nerve (Kunitake and Kannan, 2000;Petiot et al, 2001). Moreover, at this frequency, SNA oscillations are not translated into corresponding oscillations of AP because of the low-pass filter properties of the resistance vasculature .…”
Section: Introductionmentioning
confidence: 94%
“…The renal nerve contains axons of neurons that innervate blood vessels, tubules and juxtaglomerular cells in the kidney (DiBona 2000). However, as far as the baroreflex control of SNA is concerned, renal SNA (RSNA) behaves as a homogeneous population, because it is almost completely abolished during electrical stimulation of the aortic depressor nerve (Petiot et al 2001). The lumbar chain contains mostly axons of neurons supplying skeletal muscle and skin of the hindlimb.…”
Section: Sympathetic Neural Discharge In Rats (A ) General Consideratmentioning
confidence: 99%
“…100 ms together) plus the latency of the vascular response (approx. 500 ms) (Bertram et al 2000;Petiot et al 2001;Julien et al 2003;Chapuis et al 2004;Oréa et al 2007). At the resonance frequency, addition of the further time delay due to the low-pass filter properties of the vascular smooth muscle response causes the baroreflex effect on blood pressure to be delayed by exactly one half-period, resulting in positive feedback and potential instability in the loop.…”
Section: Sympathetic Neural Discharge In Rats (A ) General Consideratmentioning
confidence: 99%